2014
DOI: 10.1002/art.38873
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Acute Anterior Uveitis Reveals Similarities and Differences in Associations Observed With Ankylosing Spondylitis

Abstract: Objective To use high density genotyping to investigate the genetic associations of acute anterior uveitis (AAU) in patients both with and without ankylosing spondylitis (AS). Method We genotyped 1,711 patients with AAU (either primary or with AAU and AS), 2,339 AS patients without AAU, and 10,000 controls on the Illumina Immunochip Infinium microarray. We also used data on AS patients from previous genomewide association studies to investigate the AS risk locus ANTXR2 for its putative effect in AAU. ANTXR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
88
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 50 publications
(92 reference statements)
12
88
1
2
Order By: Relevance
“…Their disease tends to be much more persistent and is more likely to be associated with cataract or glaucoma. Several studies have identified genetic loci that affect the predisposition to uveitis in association with ankylosing spondylitis separately from affecting predisposition to joint disease [16,17]. These loci have not as yet been studied in the uveitis in association with psoriatic arthritis or IBD, and the rarity of these entities makes such a study difficult.…”
Section: Uveitis Prevalence In Spondyloarthritismentioning
confidence: 95%
See 1 more Smart Citation
“…Their disease tends to be much more persistent and is more likely to be associated with cataract or glaucoma. Several studies have identified genetic loci that affect the predisposition to uveitis in association with ankylosing spondylitis separately from affecting predisposition to joint disease [16,17]. These loci have not as yet been studied in the uveitis in association with psoriatic arthritis or IBD, and the rarity of these entities makes such a study difficult.…”
Section: Uveitis Prevalence In Spondyloarthritismentioning
confidence: 95%
“…These loci have not as yet been studied in the uveitis in association with psoriatic arthritis or IBD, and the rarity of these entities makes such a study difficult. In addition to HLA B27, several genetic factors such as polymorphisms in the IL-23R are common to ankylosing spondylitis, inflammatory bowel disease, psoriatic arthritis, and uveitis [16,17].…”
Section: Uveitis Prevalence In Spondyloarthritismentioning
confidence: 99%
“…The association of ERAP1 with acute anterior uveitis is stronger than its association with AS, suggesting that this pathway is even more centrally involved in uveitis pathogenesis than in AS predisposi tion. 69 In Behçet disease, the ASprotective haplotypes interact with HLA-B*51 to increase risk. Multiple weaker associations of ERAP1 have been reported with type 1 diabetes mellitus, cervical cancer, hypertension and multiple sclerosis, but these associations have yet to be demonstrated definitively, or have not been replicated in large studies.…”
Section: Aminopeptidases In Asmentioning
confidence: 99%
“…Besides the association with HLA-B27 (class I major histocompatibility complex [MHC]), evidence for an association of AAU with class II MHC genes has also been reported. 28 Recently, a high throughput genotyping method was used in a multicenter study 29 to investigate the genetic associations of AAU. The results showed that single nucleotide polymorphisms (SNPs) located in or around MHC class I or class II are associated with the susceptibility to AAU.…”
Section: Discussionmentioning
confidence: 99%